Trade, Growth, and Poverty - Kraay, Aart 1995- (The World Bank, 2001)
(June 2001) - The evidence from individual cases and from cross-country analysis supports the view that globalization leads to faster growth and poverty reduction in poor countries. To determine the effect of globalization on growth, poverty, and inequality, Dollar and Kraay first identify a group of developing countries that are participating more in globalization. China, India, and several other large countries are part of this group, so well over half the population of the developing world lives in these globalizing economies. Over the past 20 years, the post–1980 globalizers have seen large increases in trade and significant declines in tariffs. Their growth rates accelerated between the 1970s and the 1980s and again between the 1980s and the 1990s, even as growth in the rich countries and the rest of the developing world slowed. The post–1980 globalizers are catching up to the rich countries, but the rest of the developing world (the non-globalizers) is falling further behind. Next, Dollar and Kraay ask how general these patterns are, using regressions that exploit within-country variations in trade and growth. After controlling for changes in other policies and addressing endogeneity with internal instruments, they find that trade has a strong positive effect on growth. Finally, the authors examine the effects of trade on the poor. They find little systematic evidence of a relationship between changes in trade volumes (or any other measure of globalization they consider) and changes in the income share of the poorest—or between changes in trade volumes and changes in household income inequality. They conclude, therefore, that the increase in growth rates that accompanies expanded trade translates on average into proportionate increases in incomes of the poor.